Seasonal Changes and Acute Respiratory Infections at Barombong Health Center - Ummi Latifa Azzahra Maddareski; Muh. Alfian Jafar; Eny Arlini Wello; Hermianty Nasruddin; Dwi Anggita (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2026)
Acute Respiratory Infection (ARI) remains a significant public health problem in Indonesia, including in Makassar City. Seasonal variation in tropical regions may influence the occurrence of ARI through changes in environmental conditions. This study aimed to analyze seasonal patterns in Makassar City, describe the distribution of ARI cases at the Barombong Primary Health Center, and examine the relationship between seasonal changes and ARI incidence. This study employed an observational analytic design with a cross-sectional approach. Seasonal data and ARI cases in 2024 were statistically analyzed to assess their relationship. The results showed that the seasonal pattern in Makassar in 2024 consisted of two rainy seasons and one relatively long dry season. ARI cases at Barombong Primary Health Center fluctuated throughout the year, with the lowest number of cases in September and the highest in November. However, statistical analysis indicated no significant association between seasonal changes and the incidence of ARI (p = 0.442). In conclusion, seasonal changes were not significantly associated with ARI incidence at Barombong Primary Health Center. Variations in ARI cases were more strongly influenced by other factors, such as environmental conditions, behavioral factors, and individual characteristics.